Measured anxiety affects choices in experimental "clock" games. Issue 1 (March 2018) - Kang, Min Jeong; Camerer, Colin
Abstract: We measure anxiety by skin conductance response (SCR) in an economic setting. In "clock" games, six agents receive private signals when an asset's price exceeds its fundamental value. They can sell for immediate value or wait to sell at a higher value. Waiting is risky because the price crashes to a lower value when three agents sell. Anxiety could lead people to sell too quickly when the game is played dynamically over time, compared to a static version with precommitted selling. Empirically, delays are shorter in dynamic games than in payoff-equivalent static games, and are associated with anxiety as measured.